Incidental Learning and Explicit Recall in Upper Extremity Prosthesis Use: Insights Into Functional Rehabilitation Challenges. Issue 6 (1st November 2016) - Hughey, Laura; Wheaton, Lewis A.
ABSTRACT: Loss of an upper extremity and the resulting rehabilitation often requires individuals to learn how to use a prosthetic device for activities of daily living. It remains unclear how prostheses affect motor learning outcomes. The authors' aim was to evaluate whether incidental motor learning and explicit recall is affected in intact persons either using prostheses ( n = 10) or the sound limb ( n = 10), and a chronic amputee on a modified serial reaction time task. Latency and accuracy of task completion were recorded over six blocks, with a distractor task between blocks 5 and 6. Participants were also asked to recall the sequence immediately following the study and at a 24-hr follow-up. Prosthesis users demonstrate patterns consistent with implicit learning, with sustained error patterns with the distal terminal device. More intact individuals were able to explicitly recall the sequence initially, however there was no significant difference 24 hr following the study. Acute incidental motor learning does not appear to diminish task related error patterns or accompany with explicit recall in prosthesis users, which could present limitations for acute training of prosthesis use in amputees. This suggests differing mechanisms of visuospatial sequential learning and motor control with prostheses.